Anomalism, supervenience, and explanation in cognitive psychology - Rowlands, M (1989)
﻿ This thesis defends the claim that the principle of methodological solipsism can play no role in the formation of the theories of cognitive psychology. Corresponding to this negative claim, but assuming a comparatively minor role, will be the positive claim that a scientific psychology ought to deal in explanations which relate mental states in virtue of their semantic contents. The basis of the case against methodological solipsism is the claim that the explanatory properties invoked by this principle are indivlduation dependent on properties of semantic content. In Chapter I the idea of methodological solipsism will be discussed, and two forms distinguished. One of the versions of methodological solipsism identified invokes the explanatory notion of the narrow content of a mental state. The other version invokes the notion of formal or syntactic properties possessed by mental states. In both cases it will be argued that these properties can be identified only by way of the semantic contents of their associated mental states. The notion of narrow content will be discussed in Chapter II. The case against that version of methodological solipsism which invokes syntactic properties will be constructed in Chapters III-V. The latter argument constitutes the bulk of the thesis, and derives from considerations centred around the principles of anomalism, supervenience, and the relation between them. These arguments are intended to be of independent interest as solutions to certain persistent problems in the philosophy of mind.